Synthesis and Characterization of P-Cu2o Nanowires Arrays - Herrera-Diaz, F; Herrera-Diaz, F (2013)
In this work we studied the synthesis and morphological, structural and electrochemistry characterization of p-Cu2O nanowires, formed into pores of polycarbonate template (100 nm). The better wetting of the pores of the membrane was achieved when this was prepared under a head of 40 cm in height of the electrolyte solution (0.02 M Cu (OOCCH3)2+0.1 M NaOOCCH3, pH 5.79), for a period of 18 h. Nanowires obtained by electrolysis in the same solution showed a diameter of 226 nm and a length of 4.5 ?m, with an aspect ratio of 20. The structural analysis showed that the nanowires growth was polycrystalline with three planes preferential [(111), (200) and (220)]. From electrochemical and photoelectrochemical characterization it was determined that the nanostructures synthesized by this route, had a p-type semiconductor character and on the other hand, a good behavior as photocathode in front of the I3-/I- couple. © 2012 Elsevier B.V.